Church buildings "Documentation and analytic study of church buildings in Basra city" (Journal of University of Babylon for Engineering Sciences, 2018)
There are buildings with distinctive architectural values exposed to extinction and disappearing for reasons associated with neglect and abuse, or for reasons linked to aspects of climatic and other factors. One of these buildings are religious buildings, including the buildings of churches in various cities, including the cities of Iraq, which most cities contain this structural pattern of religious buildings, as it will address research into this type of buildings, as it represents the cultural stocks and architectural as well as religious, social and cultural importance.The research buildings churches in terms of emergence history and evolution and patterns of structural and highlighted Altsamama elements of these buildings, which distinguishes it from other buildings, as it touched search to many studies and proposals architectural own buildings in the churches, and through the criticism has been crystallizing research problem, namely the lack of specialized study documented Churches the city of Basra in the regions of the publican and Basra, which required Bunting buildings churches building in Basra and documented informed and Academy and the statement the most prominent characteristics and traits of architectural and urban being a part of the visual urban fabric, for the purpose of maintaining, as research found a set of conclusions and recommendations for achieving the goal of the research.